A rare case of primary central nervous system Haemangiopericytoma with extensive systemic metastases - Kamaludin, Noor Khairiah; Abu Bakar, Intan Bazilah (2022)
Haemangiopericytoma (HPC), currently known as solid fibrous tumour (SFT), is a rare and characteristically hyper-vascular tumour1. It occurs more commonly in musculoskeletal system, retroperitoneum and skin, but rarely in central nervous system (CNS), accounting for only 0.4% of primary CNS tumours and 2% of meningeal tumours2. Primary intracranial tumours rarely metastasise outside of the CNS. Herein, we report a case of extensive systemic metastases from primary CNS HPC with the used of radiology imaging, to aid in establishing the diagnosis of this rare event. A 41-year-old lady presented with abdominal distension and weight loss. Physical examination revealed enlarged liver and palpable abdominal mass. Her medical history was remarkable for primary CNS HPC which has been resected 18 years ago, with recurrence in 2017 where she had undergone another tumour resection. Abdominal ultrasonography to investigate for palpable abdominal mass revealed multiple large liver lesions where hepatoma was suspected. Abdominal computed tomography (CT) scan showed hyper-vascular masses in the liver, pancreas and bones, which are possibly representing extensive systemic metastases from primary CNS HPC (Figure 1). MRI spine subsequently confirmed extensive bony metastases with spinal canal stenosis (Figure 2). Correlation with histopathological examination of the pelvic bone lesion, the diagnosis of extensive systemic metastases from primary CNS HPC was confirmed. Patient is now under regular follow up for further management.